Mantendo a consistência na coevolução de modelos iStar e Casos de Uso na Engenharia de Requisitos - Paza, Diogo do Nascimento (2023)
Requirements Engineering is a fundamental step in software development. Organizational modeling techniques such as iStar, and functional requirements such as UML Use Case are used to elicit and document requirements. In previous works, it is proposed to derive use cases from iStar models and generate these artifacts in the JGOOSE tool (Java Goal into Object Oriented Standard Extension). However, the proposed derivation guidelines and the support tool do not guarantee the consistency of these artifacts as they evolve. This means that changes in use cases are not reflected in the iStar models used as a base. This deficiency can lead to inconsistent documents throughout the software lifecycle. In this way, it is proposed consistency guarantee rules to define transformations and coevolution between a use case model and an iStar model.